Tensile strength behavior of laminated veneer lumber / Zakiah Ahmad … [et al.] - Ahmad, Zakiah; Mohd Noh, Mohd Salleh; Md Tahir, Paridah; P.S, Eric (2002)
Tensile strength behavior of laminated veneer lumber (LVL) manufactured from Malaysian tropical timber was evaluated. The 50 mm thick LVL panels were manufactured using 13 and 17 layers veneers. The tensile strength test was carried out using in-grade size specimens. In order to carry out this test, a special tensile grip was fabricated using the model suggested in ASTM D198. The LVL comprised Kedondong (Canarium,spp), Keruing (Dipterocarpus, spp) and Bintagor (Calophyllum, spp). Tests were conducted according to ASTM D198 (Static Test of Lumber in Structural Size). The tensile strength properties evaluated include tensile strength, modulus of elasticity and Poisson ratio. Effect of timber species and the number of veneer layers on the tensile strength properties were analysed statistically. In this study it was found that the species has more dominant effect on the tensile strength of LVL.